1994
DOI: 10.1038/bjc.1994.283
|View full text |Cite
|
Sign up to set email alerts
|

n-3 and n-6 fatty acid processing and growth effects in neoplastic and non-cancerous human mammary epithelial cell lines

Abstract: The type rather than the amount of dietary fat may be more important in breast carcinogenesis. While animal studies support this view, little is known about the effects of essential fatty acids (EFAs) at the cellular level. The MCF-7 breast cancer and the MCF-10A non-cancerous human mammary epithelial cell lines are compared in terms of growth response to EFAs and ability to incorporate and process the EFAs. Eicosapentaenoic (EPA, n-3) and docosahexaenoic (DHA, n-3) acids, presented bound to albumin, inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
99
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 40 publications
11
99
0
Order By: Relevance
“…27,47,48 In postmenopausal women in cohort studies, decreased risk was associated with higher compositions of n-6 PUFAs and 18:2n-6, but not AA. 26,48 The AA cascade is suggested to play critical roles in tumor development from laboratory studies, [1][2][3]6 but an inverse association with breast cancer risk was unexpectedly here found for erythrocyte composition of AA. On the other hand, erythrocyte ratios of AA/EPA and AA/ DHA had positive links with risk and the findings support the hypothesis regarding competitive inhibition for biosynthesis of AAderived eicosanoids such as prostaglandin E 2 .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…27,47,48 In postmenopausal women in cohort studies, decreased risk was associated with higher compositions of n-6 PUFAs and 18:2n-6, but not AA. 26,48 The AA cascade is suggested to play critical roles in tumor development from laboratory studies, [1][2][3]6 but an inverse association with breast cancer risk was unexpectedly here found for erythrocyte composition of AA. On the other hand, erythrocyte ratios of AA/EPA and AA/ DHA had positive links with risk and the findings support the hypothesis regarding competitive inhibition for biosynthesis of AAderived eicosanoids such as prostaglandin E 2 .…”
Section: Discussionmentioning
confidence: 61%
“…Feeding studies with dietary supplementation of fish, fish oil, EPA and DHA have confirmed corresponding changes in biomate- One case and eight control subjects were excluded from analyses (see Table 1). ORs and their 95% CIs were adjusted for BMI (continuous), habitual exercise, drinking and smoking status, green-yellow vegetable intake (g/1000 kcal), menopausal status (pre-or post-menopause), family history of breast cancer in parents and/or siblings (yes or no), age at menarche ( 12, 13-14 or 15 years), menopausal periods (continuous), parity (0, 1, 2 or 3) and hormone users (yes or no).-2 Meat included beef, pork and poultry.- 3 Dietary intakes of each fatty acid group were explained in ''Material and methods'' and mainly composed of the selected 13 fatty acids as follows; SFAs (saturated fatty acids) 5 14:0 1 16:0 1 18:0; MUFAs (monounsaturated fatty acids) 5 16:1n-7 1 18:1n-9; PUFAs (polyunsaturated fatty acids) 5 n-6 PUFAs 1 n-3 PUFAs; n-6 PUFAs 5 18:2n-6 1 18:3n-6 1 20:3n-6 1 20:4n-6 (arachidonic acid, AA); n-3 PUFAs 5 18:3n-3 1 n-3 highly unsaturated fatty acids (HUFAs); and n-3 HUFAs 5 20:5n-3 (eicosapentaenoic acid, EPA) 1 22:5n-3 1 22:6n-3 (docosahexaenoic acid, DHA). NS; Not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of previous studies using either cultured cells (examples : Begin et al, 1986;Canuto et al, 1991;Grammatikos et al, 1994;Maehle et al, 1995;Padma and Das, 1996) or whole animals (examples: Borgeson et al, 1989;Pritchard et al, 1989; Gonzalez et al, 1991; have indicated that an increased exposure to the types of HPUFAs found in fish oil, especially eicosapentanoic acid, kills a variety of cancer cells without killing normal cells, and that addition of an iron-containing compound may increase cell death. However, the question still remains as to whether the most important cause of tumour regression and cell death is: (1) induction of lipid peroxidation; (2) alteration of eicosanoid production; (3) some other mechanisms associated with the alteration in membrane fatty acids or (4) the addition of iron to the diet or culture media.…”
mentioning
confidence: 99%
“…Treatment of MCF-10A cells with 6-30 ÎŒM linolenate had largely no effect, although a decrease in viability was observed at the highest concentration. The effect was observed whether linolenate was supplied as a free fatty acid bound to albumin, or as a phospholipid enriched lysosome [80]. 25-100 ÎŒM linolenate also decreased the proliferation of the MDA-MB-231 breast cancer cells in a dose dependent manner [81].…”
Section: Linolenatementioning
confidence: 99%